ANALISIS PENGARUH BETA, UKURAN PERUSAHAAN, DAN RASIO BOOK TO MARKET TERHADAP RETURN SAHAM (STUDI KASUS PADA PERUSAHAAN SEKTOR CONSUMER GOODS PERIODE 2008 – 2011) - Ali Sadikin (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2015)
Investment is rational action did by humans to increase their wealth in the future, with sacrifice money and other economic resources in investing there are some things that should be considered by investors one of which is the return and risk. In general, investors will always consider the trade off between return that will be earned in investing and the risks to be faced in making such investments. The object of this study was the Consumer Goods sector Manufacturing industries listed in the Indonesia Stock Exchange for 4 years, from 2008 to 2011. The method of selecting samples in this research is purposive judgment sampling method. The F-test was 0,000 which is smaller than the degree of error is equal to 0.05 or 5% thus Beta, company size, and the ratio of book to market simultaneously - significant effect in predicting Return Consumer Goods shares in the company. T test results showed the Beta coefficient of 0.023 with a significance value of 0.004. This means Beta significant positive effect due to the significance value of 0.004 is smaller than the required significance level of 5%. Company size coefficient of 2.349 and 0.915 significance value. This means that the size of the company does not have a significant effect because the significance value of 0.915 is much larger than the required significance level of 5%. Coefficient of book to market ratios of -0.015 with a significance value of 0.001. This means that the ratio of book to market significant negative effect because the significance value 0.001 is much smaller than the required significance level of 5%. Key words : Beta, Firm size, Market to book ratio, and Stock Retuns.